High-pressure-resistant lead-barium titanate-based thermal sensitive ceramic and preparation method thereof
By adopting the preparation method of core-shell structure, combined with ball milling, spray drying, calcining, granulation and sintering, the problem of insufficient energy consumption and pressure resistance of lead barium titanate-based PTC ceramic materials in the field of new energy vehicles is solved, and ceramic materials with high pressure resistance and excellent PTC effect are achieved.
Patent Information
- Application Number
- CN202510065664.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-29
AI Technical Summary
The application of existing lead barium titanate-based PTC ceramic materials in the field of new energy vehicles is limited by the difficulty in controlling energy consumption and the problem of frying, and their pressure resistance is insufficient, which affects the PTC effect and pressure resistance.
The core-shell structure is prepared by adopting the method of preparing the core-shell structure. The core layer is composed of lead tetraoxide, barium carbonate, titanium dioxide, manganese oxide and niobium oxide. The shell layer is composed of barium compounds, titanium compounds, strontium compounds, calcium compounds, zirconium oxychloride and tin compounds. Ceramic materials are prepared by ball milling, spray drying, calcining, granulation and sintering.
The high pressure resistance characteristics and excellent PTC effect of ceramic materials are achieved, while the ceramic grain size is refined, and the denseness and pressure resistance of the material are improved.
Smart Images

Figure CN119899030A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material science, and in particular to a high-pressure resistant barium lead titanate-based thermal sensitive ceramic and a preparation method thereof. Background Art
[0002] The research on barium titanate-based PTC (positive temperature coefficient) ceramic materials can be traced back to the 1960s. In 1950, Heyman and others from Philips Company of the Netherlands added rare earth elements to BaTiO3 materials for semiconductor experiments and found that this semiconductor material has a large positive temperature coefficient, which is the so-called PTC effect, thus setting off a wave of research on the mechanism of the PTC effect. In order to better put barium titanate-based PTC ceramics into production applications, the study found that Pb-doped barium titanate-based PTC ceramics have a very high Curie temperature and excellent PTC effect, and have a very broad application prospect.
[0003] In recent years, with the rapid development of new energy electric vehicles, lead barium titanate-based PTC thermistor ceramic materials have been widely used in automotive battery heating systems and air conditioning heating systems due to their high heating efficiency, energy saving, good stability and low production cost. Although PTC materials have the above advantages, their energy consumption is difficult to control when actually used in new energy vehicles, and there is a problem of chip frying, which greatly limits the application of PTC materials in the field of high power. Studies have found that improving the pressure resistance of PTC ceramic materials can effectively reduce the failure rate, and its heating is more stable. Therefore, it is very necessary to optimize the performance of lead barium titanate-based PTC ceramic materials and improve the pressure resistance of ceramics in the field of new energy vehicles.
[0004] In order to improve the pressure resistance of PTC ceramic materials, a lot of research has been done at home and abroad. Related studies have found that the pressure resistance of PTC ceramics is closely related to its density and grain size; by adding sintering aids, modifying doping, and adjusting the preparation process to improve the density of ceramic materials and improve the grain size, the pressure resistance of ceramic materials can be improved. Li Yongfeng et al. prepared Ca-doped barium lead titanate-based PTC ceramics using a sol-gel method and obtained a high-pressure PTC ceramic material with a pressure resistance greater than 270V / mm. However, its PTC effect is not ideal, and the lift-to-drag ratio is only 10 2Gao Pan and others studied the effects of microwave sintering and traditional sintering methods on barium titanate-based thermistor ceramics and found that microwave sintering can densify ceramics at a lower sintering temperature, making the grain distribution more uniform and the voltage resistance higher. Gao et al. used 100nm barium titanate powder as a precursor and adopted a two-step sintering method. They kept the temperature at high temperature for a short time and quickly cooled it to a lower sintering temperature. The liquid phase began to solidify, thus wrapping the grains and inhibiting their growth. They prepared a 340nm grain size, a room temperature resistivity of 340Ω·cm, and a lift-to-resistance ratio of 10 4 In the research on PTC thermistors for high withstand voltage overcurrent protection, Liu Honggang proposed that the appropriate amount of Ca 2+ Replacement Ba 2+ , can improve the microstructure of the material, make the sintered body dense and increase the pressure resistance. 2+ The PTC effect is the largest when the introduction amount is 3%.
[0005] In the current research on high-voltage lead barium titanate-based thermistor ceramics, although the PTC effect of ceramics can be improved by increasing the donor-acceptor doping concentration, this improvement is not a linear relationship, but a U-shaped curve change, which makes it difficult to accurately control the donor and acceptor doping concentrations of different systems, and with the increase of donor-acceptor doping concentrations, the ceramic grain size is difficult to control, which not only affects the PTC effect of the ceramic, but also damages its withstand voltage performance. Therefore, on the basis of adding different donor-acceptor dopants to improve the semiconductivity of barium titanate-based thermistor ceramics, the key to obtaining high-voltage lead barium titanate-based thermistor ceramics is to avoid abnormal growth of ceramic grains during sintering by appropriately doping other additives, while maintaining good density. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a high-voltage resistant barium lead titanate-based thermistor ceramic and a preparation method thereof. The prepared ceramic has high voltage resistance characteristics and excellent PTC effect.
[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a high-pressure resistant barium lead titanate-based thermistor ceramic having a core-shell structure; the raw materials of the core layer are arranged in molar proportions as follows: 2 to 5 parts of lead tetroxide, 25 to 39 parts of barium carbonate, 30 to 45 parts of titanium dioxide, 0.03 to 0.3 parts of manganese oxide, and 0.2 to 0.4 parts of niobium oxide; the raw materials of the shell layer are arranged in molar proportions as follows: 1 to 15 parts of barium compounds, 5 to 20 parts of titanium compounds, 0 to 3 parts of strontium compounds, 0 to 5 parts of calcium compounds, 0.5 to 5 parts of zirconium oxychloride, and 1 to 8 parts of tin compounds.
[0008] As a preferred embodiment, the barium compound is one or more of barium nitrate, barium chloride, and barium acetate, the titanium compound is one or both of titanium tetrachloride and tetrabutyl titanate, the strontium compound is one or more of strontium nitrate, strontium chloride, and strontium acetate, the calcium compound is one or more of calcium nitrate, calcium chloride, and calcium acetate, and the tin compound is one or both of tin nitrate and tin tetrachloride.
[0009] A method for preparing the high-voltage resistant barium lead titanate-based thermistor ceramic as described above comprises the following steps:
[0010] (1) weighing a certain amount of lead tetroxide, barium carbonate, titanium dioxide, manganese oxide and niobium oxide according to the ratio of the core layer raw materials, and then placing the above substances together with anhydrous ethanol in a ceramic ball mill, and adding zirconium oxide grinding balls for ball milling, placing the ball-milled slurry in an oven at 80° C. to dry for 4 to 6 hours, and then placing it in an alumina crucible and keeping it at 1000 to 1100° C. for 2 to 4 hours, and obtaining lead barium titanate-based powder after cooling;
[0011] (2) weighing a certain amount of barium compound, titanium compound, strontium compound, calcium compound, zirconium oxychloride, and tin compound according to the ratio of the shell raw materials, and then dissolving the above compounds in deionized water to obtain a 0.2-1.5 mol / L deionized water solution;
[0012] (3) placing the barium lead titanate-based powder prepared in step (1) and the deionized water solution prepared in step (2) in a ball mill for ball milling, and then spray drying; placing the spray-dried powder in an alumina crucible, and calcining it at 950 to 1050° C. for 2 to 4 hours;
[0013] (4) placing the calcined powder in step (3) into a ball mill, adding a 5% polyvinyl alcohol aqueous solution in an amount twice the mass of the powder, ball milling and mixing, and then spray granulating to obtain granulated powder;
[0014] (5) The granulated powder of step (4) is dry-pressed and then kept at 300-500° C. for 4-10 hours for debinding, and then heated to 1250-1350° C. for 2-4 hours for sintering to obtain the barium lead titanate-based thermistor ceramic of the present invention.
[0015] Beneficial effects of the present invention: The core-shell structure prepared by the present invention with BaPbTiMnNbO3 as the core and the modified BaTiSrCaZrSnO3 as the shell can make the modified BaTiSrCaZrSnO3-based material uniformly coated on the surface of BaPbTiMnNbO3, and the ceramic grain size is effectively refined by utilizing the above-mentioned process for realizing the core-shell structure and doping of appropriate elements in the shell structure, so that the ceramic prepared by the present invention has a high Curie point and excellent PTC effect while improving its voltage resistance characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a scanning electron microscope image of the lead barium titanate-based thermistor ceramic prepared in the present invention. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Embodiment 1:
[0019] According to the molar ratio, 4 parts of lead tetroxide, 30.4 parts of barium carbonate, 42 parts of titanium dioxide, 0.1 parts of manganese oxide and 0.3 parts of niobium oxide were weighed, and then the above substances were placed in a ceramic ball mill together with anhydrous ethanol, and zirconium oxide grinding balls were added for ball milling. The ball-milled slurry was placed in an oven at 80°C and dried for 5 hours, and then placed in an alumina crucible and kept at 1050°C for 3 hours. After cooling, barium lead titanate-based powder was obtained.
[0020] 3.1 parts of barium nitrate, 7.6 parts of titanium tetrachloride, 0.5 parts of strontium nitrate, 1 part of calcium nitrate, 1 part of zirconium oxychloride, and 2 parts of tin nitrate were weighed according to the molar ratio, and then the above compounds were dissolved in deionized water to obtain a 1 mol / L deionized water solution.
[0021] The prepared barium lead titanate-based powder and a deionized water solution are placed in a ball mill for ball milling, and then spray dried; the spray dried powder is placed in an alumina crucible and calcined at 1000°C for 3 hours; the calcined powder is placed in a ball mill, and a 5% polyvinyl alcohol aqueous solution is added in a proportion of 2 times the mass of the powder, and the mixture is ball milled and spray granulated to obtain granulated powder; the granulated powder is dry pressed, and then kept at 450°C for 8 hours for debinding, and then heated to 1300°C for 3 hours for sintering to obtain the barium lead titanate-based thermistor ceramic of the present invention.
[0022] The scanning electron microscope image of the lead barium titanate-based thermistor ceramic prepared in this example is as follows: Figure 1 As shown in the figure, it can be seen that the grains have been refined. The two sides of the ceramic sample were polished, coated with ohmic silver paste and kept at 550℃ for 30 minutes to complete the electrode preparation. Subsequently, the ceramic sample was subjected to resistance-temperature test and withstand voltage test, and its performance parameters are shown in Table 1.
[0023] Embodiment 2:
[0024] According to the molar ratio, 2 parts of lead tetroxide, 25 parts of barium carbonate, 30.5 parts of titanium dioxide, 0.3 parts of manganese oxide and 0.2 parts of niobium oxide were weighed, and then the above substances were placed in a ceramic ball mill together with anhydrous ethanol, and zirconium oxide grinding balls were added for ball milling. The ball-milled slurry was placed in an oven at 80°C and dried for 4 hours, and then placed in an alumina crucible and kept at 1100°C for 2 hours. After cooling, barium lead titanate-based powder was obtained.
[0025] 9.5 parts of barium acetate, 19 parts of tetrabutyl titanate, 3 parts of strontium acetate, 0.5 parts of calcium acetate, 5 parts of zirconium oxychloride, and 1 part of tin tetrachloride were weighed according to the molar ratio, and then the above compounds were dissolved in deionized water to obtain a 1.5 mol / L deionized water solution.
[0026] The prepared barium lead titanate-based powder and a deionized water solution are placed in a ball mill for ball milling, and then spray dried; the spray dried powder is placed in an alumina crucible and calcined at 950°C for 4 hours; the calcined powder is placed in a ball mill, and a 5% polyvinyl alcohol aqueous solution is added in a proportion of 2 times the mass of the powder, and the mixture is ball milled and spray granulated to obtain granulated powder; the granulated powder is dry pressed and then kept at 500°C for 4 hours for debinding, and then heated to 1250°C for 4 hours for sintering to obtain the barium lead titanate-based thermistor ceramic of the present invention.
[0027] The two sides of the ceramic sample were polished, coated with ohmic silver paste and kept at 550°C for 30 minutes to complete the electrode preparation. The ceramic sample was then subjected to resistance-temperature test and withstand voltage test, and its performance parameters are shown in Table 1.
[0028] Embodiment 3:
[0029] According to the molar ratio, 5 parts of lead tetroxide, 15.7 parts of barium carbonate, 30 parts of titanium dioxide, 0.3 parts of manganese oxide and 0.4 parts of niobium oxide were weighed, and then the above substances were placed in a ceramic ball mill together with anhydrous ethanol, and zirconium oxide grinding balls were added for ball milling. The ball-milled slurry was placed in an oven at 80°C and dried for 6 hours, and then placed in an alumina crucible and kept at 1000°C for 4 hours. After cooling, barium lead titanate-based powder was obtained.
[0030] 9.3 parts of barium chloride, 19.3 parts of titanium tetrachloride, 1 part of strontium chloride, 0.5 parts of calcium acetate, 0.5 parts of zirconium oxychloride, and 8 parts of tin nitrate were weighed according to the molar ratio, and then the above compounds were dissolved in deionized water to obtain a 0.5 mol / L deionized water solution.
[0031] The prepared barium lead titanate-based powder and a deionized water solution are placed in a ball mill for ball milling, and then spray-dried; the spray-dried powder is placed in an alumina crucible and calcined at 1050°C for 2 hours; the calcined powder is placed in a ball mill, and a 5% polyvinyl alcohol aqueous solution is added in an amount twice the mass of the powder, and the mixture is ball-milled and spray-granulated to obtain granulated powder; the granulated powder is dry-pressed, and then kept at 350°C for 10 hours for debinding, and then heated to 1350°C for 2 hours for sintering to obtain the barium lead titanate-based thermistor ceramic of the present invention.
[0032] The scanning electron microscope image of the lead barium titanate-based thermistor ceramic prepared in this example is as follows: Figure 1 The two sides of the ceramic sample were polished, coated with ohmic silver paste and kept at 550°C for 30 minutes to complete the electrode preparation. The ceramic sample was then subjected to resistance-temperature test and withstand voltage test, and its performance parameters are shown in Table 1.
[0033] Table 1 Electrical properties of lead barium titanate based thermistor ceramics prepared by the present invention
[0034]
Claims
1. A high-voltage resistant barium lead titanate-based thermistor ceramic, characterized in that: It has a core-shell structure; the raw materials of its core layer have a molar composition of 2-5 parts of lead tetroxide, 25-39 parts of barium carbonate, 30-45 parts of titanium dioxide, 0.03-0.3 parts of manganese oxide, and 0.2-0.4 parts of niobium oxide; the raw materials of its shell layer have a molar composition of 1-15 parts of barium compounds, 5-20 parts of titanium compounds, 0-3 parts of strontium compounds, 0-5 parts of calcium compounds, 0.5-5 parts of zirconium oxychloride, and 1-8 parts of tin compounds.
2. The high-voltage resistant barium lead titanate-based thermistor ceramic according to claim 1, characterized in that: The barium compound is one or more of barium nitrate, barium chloride, and barium acetate; the titanium compound is one or two of titanium tetrachloride and tetrabutyl titanate; the strontium compound is one or more of strontium nitrate, strontium chloride, and strontium acetate; the calcium compound is one or more of calcium nitrate, calcium chloride, and calcium acetate; and the tin compound is one or two of tin nitrate and tin tetrachloride.
3. A method for preparing the high-voltage resistant barium lead titanate-based thermistor ceramic according to claim 1, comprising the following steps: (1) weighing a certain amount of lead tetroxide, barium carbonate, titanium dioxide, manganese oxide and niobium oxide according to the ratio of the core layer raw materials, and then placing the above substances together with anhydrous ethanol in a ceramic ball mill, and adding zirconium oxide grinding balls for ball milling, placing the ball-milled slurry in an oven at 80° C. to dry for 4 to 6 hours, and then placing it in an alumina crucible and keeping it at 1000 to 1100° C. for 2 to 4 hours, and obtaining lead barium titanate-based powder after cooling; (2) weighing a certain amount of barium compound, titanium compound, strontium compound, calcium compound, zirconium oxychloride, and tin compound according to the ratio of the shell raw materials, and then dissolving the above compounds in deionized water to obtain a 0.2-1.5 mol / L deionized water solution; (3) placing the barium lead titanate-based powder prepared in step (1) and the deionized water solution prepared in step (2) in a ball mill for ball milling, and then spray drying; placing the spray-dried powder in an alumina crucible, and calcining it at 950 to 1050° C. for 2 to 4 hours; (4) placing the calcined powder in step (3) into a ball mill, adding a 5% polyvinyl alcohol aqueous solution in an amount twice the mass of the powder, ball milling and mixing, and then spray granulating to obtain granulated powder; (5) The granulated powder of step (4) is dry-pressed and then kept at 300-500° C. for 4-10 hours for debinding, and then heated to 1250-1350° C. for 2-4 hours for sintering to obtain the barium lead titanate-based thermistor ceramic of the present invention.
Citation Information
Patent Citations
Dielectric ceramic particle, and preparation method and application of dielectric ceramic particle
CN104318980A
Ceramic dielectric material of barium titanate core-strontium / zirconium / calcium shell structure and preparation method thereof
CN107739205A
Cold conductor material used for electronic switches consists of a finely dispersed titanate powder and a structure made up of a core of lead titanate and a shell of barium titanate, calcium titanate or strontium titanate
DE10045394A1
Cited By
High-voltage-resistant PTC (Positive Temperature Coefficient) ceramic heating chip
CN122205665A